2022
DOI: 10.14740/jmc3883
|View full text |Cite
|
Sign up to set email alerts
|

Severe Gastroparesis Flare: Is COVID-19 the Inciting Factor?

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection has emerged as a public health hazard. It is commonly associated with respiratory symptoms including fever, cough and sore throat. Viral infections have historically been implicated in the exacerbations of gastrointestinal (GI) disorders. Coronavirus disease 2019 (COVID-19) has been associated with GI manifestations including diarrhea and vomiting. However, exacerbation of underlying functional GI disorders has been rarely reported with SAR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0
13

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 20 publications
0
1
0
13
Order By: Relevance
“…Preclinical studies demonstrated the ability of aqueous extract of C. cassia Presl bark (150 and 300 mg/kg) to enhance gastric emptying and to promote GI transit that are both delayed in some Long COVID‐19 patients, suffering from a complex pathological picture‐defined autoimmune GI dysmotility (Montalvo et al, 2022; Sebai et al, 2019). These effects may be relevant also in patients with SARS‐CoV‐2‐induced gastric motility alterations (Patel et al, 2022; Rusch et al, 2022). Furthermore, in vivo experiments have shown that water extracts derived from the bark of C. cassia (150 mg/kg) significantly reduce the extent of gastric mucosa injuries caused by indomethacin, NSAIDs, ethanol, and ethanol/hydrochloric acid.…”
Section: The Phytocomplexmentioning
confidence: 99%
“…Preclinical studies demonstrated the ability of aqueous extract of C. cassia Presl bark (150 and 300 mg/kg) to enhance gastric emptying and to promote GI transit that are both delayed in some Long COVID‐19 patients, suffering from a complex pathological picture‐defined autoimmune GI dysmotility (Montalvo et al, 2022; Sebai et al, 2019). These effects may be relevant also in patients with SARS‐CoV‐2‐induced gastric motility alterations (Patel et al, 2022; Rusch et al, 2022). Furthermore, in vivo experiments have shown that water extracts derived from the bark of C. cassia (150 mg/kg) significantly reduce the extent of gastric mucosa injuries caused by indomethacin, NSAIDs, ethanol, and ethanol/hydrochloric acid.…”
Section: The Phytocomplexmentioning
confidence: 99%
“…Пациентку выписали из стационара на 11-й день с 2-недельным курсом антикоагулянтной терапии и метоклопрамида. При повторном визите к гастроэнтерологу пациентка сообщила об улучшении состояния [72].…”
Section: постковидное поражение пищеварительной систему у пациентов с сдunclassified
“…A partir de dezembro de 2019 a infecção por SARS-CoV-2 começou a se espalhar rapidamente causando uma pandemia com grande morbidade e mortalidade, e grande impacto a sistemas de saúde ao redor do mundo (Chen et al, 2021). A doença causada por este patógeno foi chamada de COVID-19 e considerada inicialmente uma doença respiratória, causando desde sintomas de resfriado moderado a pneumonia viral grave (Chen et al, 2021;Patel et al, 2022;Song et al, 2021). Com melhor entendimento da doença, percebeu-se que outros sistemas podem ser afetados, podendo haver manifestações neurológicas, renais, cardiológicas, hematopoiéticas e gastrointestinais (Chen et al, 2021;Patel et al, 2022;Deb et al, 2022;Gubatan et al, 2022).…”
Section: Introductionunclassified
“…A doença causada por este patógeno foi chamada de COVID-19 e considerada inicialmente uma doença respiratória, causando desde sintomas de resfriado moderado a pneumonia viral grave (Chen et al, 2021;Patel et al, 2022;Song et al, 2021). Com melhor entendimento da doença, percebeu-se que outros sistemas podem ser afetados, podendo haver manifestações neurológicas, renais, cardiológicas, hematopoiéticas e gastrointestinais (Chen et al, 2021;Patel et al, 2022;Deb et al, 2022;Gubatan et al, 2022). Cerca de metade dos pacientes infectados por SARS-CoV-2 apresentam sintomas gastrointestinais durante a fase aguda, como diarreia (manifestação mais comum), náuseas, vômitos e dor abdominal (Deb et al, 2022;Gubatan et al, 2022;Silva et al, 2020).…”
Section: Introductionunclassified
See 1 more Smart Citation